(untitled) (Research, Society and Development, 2021)
Vitamin D has multiple functions and its main ways to obtain it are through sun exposure and from the intake of food sources or supplementation. However, it is observed that even people with longer exposure to the sun have reduced levels of this hormone, and food intake can be an alternative. It is speculated that people with metabolic syndrome (MS) and/or obesity are more susceptible to hypovitaminosis D than people without such factors. The aim of this study is to assess dietary intake of vitamin D and compare it with its serum levels between people with MS and without MS. Methodology: Comparative study with 104 volunteers divided into two groups (a group of people with MS and another group of people without MS) of equal size. Anthropometric evaluation (body mass index (BMI) and waist circumference (WC)) and biochemical tests (HDL-c, triglycerides, fasting glucose and vitamin D) were performed. Serum vitamin D levels were assessed by measuring 25-hydroxyvitamin D and intake determined from dietary recall. Results: Mean serum levels in participants without MS was higher (30.602 ng/mL) than with MS (26.296 ng/mL). Mean vitamin D intake was lower in people with MS (1.61µ) than without MS (2.18µ). Conclusion: All participants had insufficient dietary intake of vitamin D and, consequently, low serum levels, even with adequate sun exposure. Public policies are needed to encourage consumption of source foods and to fortify staple foods.